The Value of Spiritual and Social Education in Surah Al-Maun and Its Relevance to Learning the History of Islamic Culture - Zikri Azizan; Achyar Zein; Yusnaili Budianti (Yupa: Historical Studies Journal, 2023)
The purpose of this study is to describe the value of spiritual and social education in Surah Al-Maun and its relevance to learning the history of Islamic culture. The research method used is descriptive qualitative research. Data was collected by means of literature study, document analysis, observation and interviews. Data analysis adopted the interactive model of Miles and Huberman. The results showed that Surah Al Ma'un contains spiritual and social values such as religious liars, woe to those who pray, people who are negligent in their prayers, people who do riya, people who rebuke orphans, does not recommend feeding the poor, reluctant to help with useful goods. So that these values are relevant to the subject of Islamic cultural history which aims to prepare students to recognize, understand, appreciate the history of Islamic culture which then becomes the basis of the way of life through guidance, teaching, training, use of knowledge and habituation.